2013
DOI: 10.1002/ca.22250
|View full text |Cite
|
Sign up to set email alerts
|

Innervation pattern of the suprascapular nerve within supraspinatus: A three‐dimensional computer modeling study

Abstract: The relationship between the innervation pattern of the suprascapular nerve (SSN) and the muscle architecture of supraspinatus has not been thoroughly investigated. The supraspinatus is composed of two architecturally distinct regions: anterior and posterior. Each of these regions is further subdivided into three parts: superficial, middle and deep. The purpose of this study was to investigate the course of the SSN throughout the volume of supraspinatus and to relate the intramuscular branches to the distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Although growing evidence suggests that the anterior and posterior regions of supraspinatus are functionally distinct (Roh et al 2000;Kim et al 2007Kim et al , 2013Hermenegildo et al 2014), EMG activity of only the anterior portion of the muscle has been studied previously and this has been considered to be representative of the entire muscle. To the best of our knowledge, in vivo activity of the posterior region has not been assessed; thus, its contribution to modulating force postures that may elicit maximal activation of the posterior region, we assessed two types of exertions: abduction and external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Although growing evidence suggests that the anterior and posterior regions of supraspinatus are functionally distinct (Roh et al 2000;Kim et al 2007Kim et al , 2013Hermenegildo et al 2014), EMG activity of only the anterior portion of the muscle has been studied previously and this has been considered to be representative of the entire muscle. To the best of our knowledge, in vivo activity of the posterior region has not been assessed; thus, its contribution to modulating force postures that may elicit maximal activation of the posterior region, we assessed two types of exertions: abduction and external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent morphological studies have revealed that the supraspinatus muscle (SSP) consists of two distinct subregions and have suggested that the functions of these subregions differ (Vahlensieck et al, ; Rho et al, ; Gates et al ; Ackland and Pandy, ). More recently, Kim et al () divided the SSP into six subregions using the three‐dimensional dissection technique; this subdivision was subsequently supported by the intramuscular nerve branching study by Hermenegildo and Roberts (). These researchers also tried to elucidate the differences among the subregions using ultrasound sonography, specifically in terms of the fiber length and pennation angle, but did not totally clarify their respective functions (Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the articular branches of SSN innervating the posterosuperior GHJ capsule were found to originate from the lateral trunk of SSN. The motor branches of the medial and lateral trunks of SSN supply the anterior and posterior regions of supraspinatus, respectively 21. In a follow-up study, Kim et al 22 suggested that the anterior region is responsible for shoulder abduction while the posterior region plays a greater role in joint stabilization 22.…”
Section: Discussionmentioning
confidence: 99%